Comparison between the difficulty of laparoscopic limited liver resections of tumors located in segment 7 versus segment 8: An international multicenter propensity‐score matched study. (20th July 2022) - Efanov, Mikhail; Salimgereeva, Diana; Alikhanov, Ruslan; Wu, Andrew G. R.; Geller, David; Cipriani, Federica; Aghayan, Davit L.; Fretland, Asmund Avdem; Sijberden, Jasper; Belli, Andrea; Marino, Marco V.; Mazzaferro, Vincenzo; et al.
Abstract: Background: Presently, according to different difficulty scoring systems, there is no difference in complexity estimation of laparoscopic liver resection (LLR) of segments 7 and 8. However, there is no published data supporting this assumption. To date, no studies have compared the outcomes of laparoscopic parenchyma‐sparing resection of the liver segments 7 and 8. Methods: A post hoc analysis of patients undergoing LLR of segments 7 and 8 in 46 centers between 2004 and 2020 was performed. 1:1 Propensity score matching (PSM) was used to compare isolated LLR of segments 7 and 8. Subset analyses were also performed to compare atypical resections and segmentectomies of 7 and 8. Results: A total of 2411 patients were identified, and 1691 patients met the inclusion criteria. Comparison after PSM between the entire cohort of segment 7 and segment 8 resections revealed inferior results for segment 7 resection in terms of increased blood loss, blood transfusions, and conversions to open surgery. Subset analyses of only atypical resections similarly demonstrated poorer outcomes for segment 7 in terms of increased blood loss, operation time, blood transfusions, and conversions to open surgery. Conversely, a subgroup analysis of segmentectomies after PSM found better outcomes for segment 7 in terms of a shorter operation time and hospital stay. Conclusion: Differences in the outcomes of segments 7 and 8 resections suggest a greater difficulty of laparoscopic atypical resection of segment 7 compared to segment 8, and greater difficulty of segmentectomy 8 compared to segmentectomy 7.